Principles and Conditions for the Determination of Age and Khyar-ul-Bulugh (option of puberty) in Marriage: A Jurisprudential Comparative Study: نكاح میں تعیینِ عمر اور خیارِ بلوغ کی شرائط وضوابط: فقہی و تقابلی مطالعہ - Shaheen, Ghulam Dastgeer; Abbas, Hafiz Ghulam; Hussain, Khalid (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Marriage is the first universal social institution and the gateway to establishing a new family institution. Marital life is a pivotal variable in the socio-economic development of society. Legal requirements for marriage differ from state to state. Muslim Family Laws declare the consent of the parties as essential for a valid marriage. The determination of age with the principle of Khyar-ul-Bulugh (option of puberty) is a debatable topic among Muslim scholars. Muslim countries, including Pakistan, enacted a law on it but missed the fundamental principle of Khyar-ul-Bulugh. It is critical to study both principles concurrently. This topic has no concrete determination in divine texts but pended on discretion. It requires a jurisprudential comparative course to understand its spirit. This paper investigates jurisprudential studies on the determination of age and the concept of option of puberty. It examines various interpretations having relevance to society. It denotes the principles and conditions against this concept. It, finally, makes certain recommendations to introduce effective legislation and amendments.